Pegylated interferon therapy during early pregnancy for hepatitis B infection: does it prevent vertical transmission?. (19th March 2017) - Atasoy, Halil Ibrahim; Sirmatel, Pinar; Sirmatel, Fatma
Abstract: In general, interferon (IFN) is avoided during pregnancy due to the possibility of fetal side effects. We, herein, reported two child-bearing women with chronic hepatitis B (HB) infection who used pegylated interferon alfa 2b (PEG IFNα 2b) in first trimester unintentionally. We compared HB contracting rates of gestations in which IFN was used and not used. The cases are unique in that they could highlight the importance of IFN use in early gestation for preventing vertical transmission particularly if combined with antiviral therapy for the rest of pregnancy.